2020
DOI: 10.3389/fneur.2020.00596
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Review and Meta-analysis of the Therapeutic Effect of Acupuncture on Migraine

Abstract: Background: Migraine is an intractable headache disorder, manifesting as periodic attacks. It is highly burdensome for patients and society. Acupuncture treatment can be beneficial as a supplementary and preventive therapy for migraine. Objectives: This systematic review and meta-analysis aimed to investigate the efficacy and safety of acupuncture for migraine, and to examine transcranial doppler changes after acupuncture. Methods: Reports, conference, and academic papers published before March 15, 2019 in dat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Migraine is typically treated by various pharmacological or non-pharmacological therapies to relieve pain or prevent migraine attacks (Tfelt-Hansen, 2013 ). Although commonly used drugs, such as triptans, ergotamine preparations, and barbiturates, have achieved positive therapeutic effects in the treatment of migraine (Farri et al, 2012 ; Ou et al, 2020 ), side effects, such as weight gain, fatigue, sleep disturbance, gastrointestinal intolerance, and medication overuse headache, are common in patients with long-term use (Silberstein et al, 2012 ; Tfelt-Hansen, 2013 ). Hence, non-pharmacological therapies with less adverse effects that have a supplementary and preventive action are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Migraine is typically treated by various pharmacological or non-pharmacological therapies to relieve pain or prevent migraine attacks (Tfelt-Hansen, 2013 ). Although commonly used drugs, such as triptans, ergotamine preparations, and barbiturates, have achieved positive therapeutic effects in the treatment of migraine (Farri et al, 2012 ; Ou et al, 2020 ), side effects, such as weight gain, fatigue, sleep disturbance, gastrointestinal intolerance, and medication overuse headache, are common in patients with long-term use (Silberstein et al, 2012 ; Tfelt-Hansen, 2013 ). Hence, non-pharmacological therapies with less adverse effects that have a supplementary and preventive action are needed.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, results from accumulating high quality clinical evidences have supported the use of acupuncture for pain relief ( 27 30 ). In fact, this therapy is now widely accepted as a safe and efficacious strategy for migraine prevention, but the effect of verum over sham acupuncture is only moderate ( 13 , 31 ). This finding has been corroborated by results from several large-scale meta-analyses targeting acupuncture treatment for chronic pain conditions ( 32 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, a series of scientific evaluations have been conducted on the efficacy and safety of acupuncture in treating migraine 10,26. Currently, increasingly more evidence supports the use of acupuncture in migraine patients 44,45. Although a number of previous systematic reviews have confirmed the clinical efficacy and safety of acupuncture for migraine, evaluations focusing only on acupuncture versus sham acupuncture are rare.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 26 Currently, increasingly more evidence supports the use of acupuncture in migraine patients. 44 , 45 Although a number of previous systematic reviews have confirmed the clinical efficacy and safety of acupuncture for migraine, evaluations focusing only on acupuncture versus sham acupuncture are rare. In this review, the findings indicated that acupuncture was superior to sham acupuncture for migraine treatment.…”
Section: Discussionmentioning
confidence: 99%